Holistic approach to human resources and organizational acceleration. Issue 2 (11th April 2016) - Pluta, Anna; Rudawska, Aleksandra
Abstract : Purpose: – The purpose of this paper is to propose holistic approach to human resources in the situation of organizational acceleration. Authors are postulating that the holistic approach to HR helps in maintaining sustainable individual resources of employees in the situation of continuous organizational changes and time pressure that further can prevent from the individual resources exhaustion. Design/methodology/approach: – This conceptual paper builds on the problem of occupational stress that is connected with organizational acceleration. Authors define stress as the individually perceived inability to match expectations caused by the deficiency of individual resources. They conceptualize the individual resources of employees basing on the concepts of human capital and the individual energy at work and propose a framework of individual resources of employees that enables holistic view of an individual in an organization. Findings: – In the situation of organizational acceleration HRM function plays important role in sustaining individual resources of employees in order to minimize threat of occupational stress and further burnout. HR practices should apply multidimensionality of individual resources and threat it holistically aiming at sustaining all four potentials – spiritual, intellectual, emotional and physical. Research limitations/implications: – Authors indicate that managers need to understand how to deal with the acceleration in order to overcome the negative consequences for individuals. There is still need for identifying HR practices that are the key success factors in the situation of organizational acceleration. Originality/value: – Authors take up the current problem of organizational acceleration from the individual perspective. They propose a concept of individual resources of employees and connected to it holistic approach to HR in the times of great time pressure, work overload, occupational stress and burnout threat.